Quality service delivery in cardiac rehabilitation: cross-cultural challenges in an Australian setting - Haghshenas, Abbas; Davidson, Patricia (Radcliffe Medical Press Ltd., 2011)
Background: Cardiac rehabilitation is an evidence-based health service model for providing secondary prevention strategies following an acute cardiac event. In spite of the benefits of cardiac rehabilitation, there are striking cultural and ethnic disparities with regard to access to and usage of these programmes. Objective: To investigate the challenges in providing cardiac rehabilitation to culturally diverse populations in Australia to inform culturally competent care. Method: This was a qualitative study using interviews with 25 health professionals from diverse professional and language backgrounds working in cardiac rehabilitation and participant observation of educational and counselling sessions in four cardiac rehabilitation programmes in metropolitan Sydney, Australia. Results: Providing cardiac rehabilitation to patients from culturally and linguistically diverse backgrounds presented greater challenges than did provision to the mainstream population. These challenges resulted from the interaction of multiple and complex factors such as patients, providers, structural and organisational characteristics within the treatment setting. Communication issues, reconciling health messages with culturally specific issues such as diet, social and family structure and implementation of self-management strategies are significant challenges. Conclusion: Strategies are needed to overcome cross-cultural challenges and ensure effective and equitable cardiac rehabilitation service delivery.